2018
DOI: 10.4172/2573-4598.1000140
|View full text |Cite
|
Sign up to set email alerts
|

Post Ischemic Stroke Complication: How Much Nursing Diagnosis are Confirms by Neurologist?

Abstract: Background: Nursing role in post ischemic stroke is vulnerable by correct nursing recognition, due to limited study and evaluation of, this study was conducted. Material and method: It was a retrospective cross-sectional study that all patients admitted with a diagnosis of ischemic stroke in the Ayatollah Rouhani Hospital of Babol from 2015 to 2016. Data was analyzed by chi-square, t-test and coefficient, Kappa tests in spss21. Results: Of 300 ischemic stroke patients were studied, Distribution of sex was 154 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 20 publications
(38 reference statements)
1
3
0
Order By: Relevance
“…The current study stated that; the most common type of stroke among both groups was ischemic stroke; the result consistent with the study conducted by [18] they reported that; ischemic stroke is the greatest type among patients. The present study revealed that; diabetes mellitus is the most common comorbidity for incidence of stroke among both groups; this result agreed with [19] who said that; hyperglycemia is the major risk factor of stroke incidence.…”
Section: As Regards To Demographic Characteristics and Medical Datasupporting
confidence: 90%
“…The current study stated that; the most common type of stroke among both groups was ischemic stroke; the result consistent with the study conducted by [18] they reported that; ischemic stroke is the greatest type among patients. The present study revealed that; diabetes mellitus is the most common comorbidity for incidence of stroke among both groups; this result agreed with [19] who said that; hyperglycemia is the major risk factor of stroke incidence.…”
Section: As Regards To Demographic Characteristics and Medical Datasupporting
confidence: 90%
“…Therefore, astrocyte and glial cells act as bridge interaction between neurons and immune system through different pro-inflammatory cytokines, Figure 4 [49]. It has been shown that inflammatory changes, glial and astrocyte activations at poststroke period participating together in the induction of different PIS complications such as depression, epilepsy, dementia and cognitive dysfunctions [50]. Vardian study illustrated that VPN have noteworthy antioxidant, anti-inflammatory and anti-apoptotic effects with inhibitory effect on glial and astrocyte cells during and following IS.…”
Section: Effects Of Vinpocetine On Proiinflammatory Mediators During mentioning
confidence: 99%
“…Four out of five strokes occur in low-and middle-income countries. The World Health Organization predicts by the end of 2020, stroke will be the second cause of death after ischemic heart disease in developing and developed countries (Ahangar et al, 2018& World Heart Federation, 2018. In Egypt stroke accounts for 6.4% of all deaths and thus ranks the third after heart disease and gastrointestinal diseases with a crude prevalence rate of 963/100000 inhabitants.…”
Section: Significance Of the Studymentioning
confidence: 99%